Sobre o meio do altar : os sacrários produzidos na região centro-sul das Minas Gerais setecentistas - Sabrina Mara Sant’Anna (2015)
The present thesis deals with the Holy Sacrament´s house, being its subject the sacrarium fixed on the middle of the altar. The research has considered mainly the artistic composition (iconography, symbolism and form) of the eucharistic tabernacles of six important 18th century parochial seats, raised on Minas Gerais South Midlands, as follows: Mother Church of Nossa Senhora da Conceição (Vila Real de Nossa Senhora do Sabará, nowadays the city of Sabará); Mother Church of Nossa Senhora da Conceição (Vila do Ribeirão do Carmo / Cathedral of Nossa Senhora da Assunção and city of Mariana from 1745 onwards); Mother Church of Nossa Senhora do Pilar (Vila Rica, Ouro Preto); Mother Church of Nossa Senhora da Conceição (Vila Rica, Ouro Preto); Mother Church of Nossa Senhora do Pilar (Vila de São João d´El Rey, São João del-Rei) and Mother Church of Santo Antônio (Vila de São Jose d´El Rey, Tiradentes). Noteworthy is the fact that the cases selected for study were conceived as constituent parts of retables erected in portuguese-national and joanine style between 1710 and 1768 by Portuguese carvers. The research has demonstrated that the guideline´s kernel of the 13th chapter of Instructionum Fabricae Ecclesiasticae et Supellectilis Ecclesiasticae libri duo (a code published in 1577 by Carlos Borromeu, bishop of Milan), and the numerical symbolism taught by the clergy long since Christian antiquity, were respected and applied to the features of the Eucharistic sacraria analysed here. As for those tabernacles fixed on brotherhood altars, placed on the nave of the temples, investigation has pointed out two patterns: decorative (conceived with a false door, i. e., without hinges and lock) and functional (serving as a temporary house for the Holy Sacrament and safe for relics).